Trace amounts of poly‐β‐cyclodextrin wrapped carbon nanotubes for the microextraction of flavonoids in honey samples by capillary electrophoresis with light‐emitting diode induced fluorescence detection. Issue 13 (26th April 2016) - Xu, Jing‐Jing; An, Mingrui; Yang, Rui; Cao, Jun; Ye, Li‐Hong; Peng, Li‐Qing
Abstract : A novel dispersive micro‐SPE method with trace poly‐β‐CD wrapped multiwalled carbon nanotubes as sorbents was applied to extract flavonoids in honey samples. The analytes were then determined by CE with LED‐induced fluorescence detection. The influencing parameters, such as the sorbent concentration, extraction time, and eluent type, were properly optimized. The established method had the advantages of simplicity, low consumption of sorbent amount (0.009 mg) and organic solvent (100 μL), and high sensitivity, meeting the principle of green chemistry. Under the optimum conditions, the sorbents allowed the extraction and preconcentration of the flavonoids with enrichment factors in the range from 78 to 166. The recovery study performed at two different fortification levels provided an average recovery >91%. LODs for all the compounds ranged from 0.07 to 17.99 ng/mL. These results demonstrated that the proposed method could be used as a convenient and efficient extraction technique for analysis of flavonoids in different honey matrices.